Emotion AI as a HR Tool for Promoting Workplace Well-Being: Examining the Practical and Ethical Challenges using Efficient net - GNANADHAS Delina; BADADA Bayissa; RAMASWAMY Krishnaraj; VAIRAMANI Sathyamoorthi; SIKKANDER BASHEER Inayath Ahamed; THIRUTHUVANATHAN Michael Moses (Communications of International Proceedings, 2024)
Emotion AI, otherwise called as affective computing, a popular AI-driven tool to detect and interpret human emotions is increasingly used by business organizations around the world as a powerful tool to know, manage and monitor employees’ emotional states. Employing affecting computing practices are known to strengthen and empower employees both mentally and physically, which in turn fosters workplace well-being. This research work highlights the applicability of affective computing in the human side of workplace and its capability as a sophisticated HR tool in the modern workplace. With evidence from past research, the role of emotion AI in enhancing workplace well-being has been examined and its suitability as a HR tool for promoting well-being in the workplace has been appraised using efficientnet on emotion dataset to develop HRnet, a deep learning model. Further, a detailed analysis of the challenges employed in using it has been presented. This paper focuses on developing a robust model for Facial Emotion Recognition tailored for Human Resources applications examining theoretically, the practical and ethical challenges in its implementation. The strength of emotion AI lies in recognition, expression, modelling, communication, and response to emotion while, the practical challenges associated with its application in the workplace include inaccuracies in capturing the emotions, faux emotional manifestations, failure in reflecting the real behaviour of humans and faulty reactiveness and the ethical challenges comprise breach of personal and private space of employees in the workplace.
Keywords: Affective computing; Workplace well-being; Emotion AI; HR tool; Efficientnet; HRnet; Practical challenges; Ethical challenges